Comparing P-Selectin (CD62P) expression in patients receiving non-leukodepleted vs leukodepleted thrombocyte concentrates - Teguh Triyono; Budi Mulyono; . Sutaryo; Abdul Salam Sofro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Thrombocyte concentrate (TC) transfusion is an important supportive therapy in patients with thrombocytopenia. The risks in platelet transfusions may be related to the content of TC including the contaminant leukocytes. The aim of this study was to assess the risk of increased level of P-Selectin (CD62P) expression of non-leukodepleted TC transfusions.This was a quasi-experimental study. Subjects were children patients aged 1-18 years who received a non-leukodepleted or a leukodepleted TC transfusions. Comparison of the proportion of increased expression of CD62P in both groups expressed as relative risk. The subjects consisted of 51 patients who received non-leukodepleted and 52 patients who received leukodepleted TC transfusions. The risk of increased expression of CD62P in patients receiving non-leukodepleted TC transfusions were 2.38 (95%CI:1.60-3.53) times higher than those who received leukodepleted TC. Non-leukodepleted have significant higher risks of increased CD62P expression than leukodepleted TC transfusions.